2023
DOI: 10.3847/1538-4357/acc250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Fields on Gas Dynamics and Star Formation in Nuclear Rings

Abstract: Nuclear rings at the centers of barred galaxies are known to be strongly magnetized. To explore the effects of magnetic fields on star formation in these rings and nuclear gas flows, we run magnetohydrodynamic simulations in which there is a temporally constant magnetized inflow to the ring, representing a bar-driven inflow. The mass inflow rate is 1M ⊙ yr−1, and we explore models with a range of field strength in the inflow. We adopt the TIGRESS framework developed by Kim & Ostriker to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…If we include magnetic field in our models, this would require an even lower bar pattern speed to fit the observed shock features. On the other hand, Moon et al (2023) investigated the effects of magnetic field on the nuclear ring in barred galaxies and found that the existence of magnetic field largely suppresses the star formation on the nuclear ring and helps produce a circumnuclear disk. This may help to explain the relatively weak star formation activity in the central 500 pc of the M31 bulge (Dong et al 2018).…”
Section: Systematic Uncertainty In Gas and Stellar-dynamical Modelsmentioning
confidence: 99%
“…If we include magnetic field in our models, this would require an even lower bar pattern speed to fit the observed shock features. On the other hand, Moon et al (2023) investigated the effects of magnetic field on the nuclear ring in barred galaxies and found that the existence of magnetic field largely suppresses the star formation on the nuclear ring and helps produce a circumnuclear disk. This may help to explain the relatively weak star formation activity in the central 500 pc of the M31 bulge (Dong et al 2018).…”
Section: Systematic Uncertainty In Gas and Stellar-dynamical Modelsmentioning
confidence: 99%
“…It is also discussed how the bar potential contributes to the gas distribution and motion via the magnetic field in the Galactic center region (Kim & Stone 2012). Recently, Moon et al (2023) performed 3D MHD numerical simulations under the magnetized inflowing gas along a dust lane into the Galactic center region, which is expected from the stellar bar. They reported that the amplified magnetic field plays a substantial role in the suppression of star formation in the nuclear ring region and the excitation of inflows from the ring to the nuclear disk.…”
Section: Application To Milky Way-the Stellar Barmentioning
confidence: 99%